Penerapan Model Modifikasi UTAUT2: Perceived Risk dalam Analisis Faktor-faktor yang Berpengaruh Terhadap Niat Penggunaan Bank Digital Jago - Amelia, Tarina Putri; Kurniawan, Dedy (STIKOM Tunas Bangsa Pematangsiantar, 2024)
Digital banking is one of the digital transformations in the banking sector that is still relatively new in Indonesia. However, digital bank users are still far away when compared to conventional banks that have physical offices. Bank Jago is one example of a digital bank in Indonesia. This study aims to determine the factors that influence the intention to use Jago digital bank technology. The Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) conceptual model is used in this study by adding the Perceived Risk variable. Data collection was carried out by distributing questionnaires through social media (Twitter and Instagram) with the criteria that respondents were users or had used the Jago application. Data analysis was carried out using the Partial Least Squares Path Modeling (PLS-SEM) method. The results showed that the intention to use the Jago digital bank was significantly influenced by hedonic motivation, habit, performance expectancy, price value, and perceived risk; while effort expectancy, facilitating conditions, and social influence did not have a significant influence on the intention to use Bank Jago